Improving cognitive control: Is theta neurofeedback training associated with proactive rather than reactive control enhancement?. (6th July 2021) - Eschmann, Kathrin C. J.; Mecklinger, Axel
Abstract: Frontal‐midline (FM) theta activity (4–8 Hz) is proposed to reflect a mechanism for cognitive control that is needed for working memory retention, manipulation, and interference resolution. Modulation of FM theta activity via neurofeedback training (NFT) demonstrated transfer to some but not all types of cognitive control. Therefore, the present study investigated whether FM theta NFT enhances performance and modulates underlying EEG characteristics in a delayed match to sample (DMTS) task requiring mainly proactive control and a color Stroop task requiring mainly reactive control. Moreover, temporal characteristics of transfer were explored over two posttests. Across seven 30‐min NFT sessions, an FM theta training group exhibited a larger FM theta increase compared to an active control group who upregulated randomly chosen frequency bands. In a posttest performed 13 days after the last training session, the training group showed better retention performance in the DMTS task. Furthermore, manipulation performance was associated with NFT theta increase for the training but not the control group. Contrarily, behavioral group differences and their relation to FM theta change were not significant in the Stroop task, suggesting that NFT is associated with proactive but not reactive control enhancement. Transfer to both tasks at a posttest one day after training was not significant. Behavioral improvements were not accompanied by changes in FM theta activity, indicating no training‐induced modulation of EEG characteristics. Together, these findings suggest that NFT supports transfer to cognitive control that manifests late after training but that other training‐unspecific factors may also contribute to performance enhancement. Abstract : The present study suggests a relationship between upregulation of frontal‐midline theta activity via neurofeedback training and enhancement of proactive rather than reactive control processes, even though other factors, such as task repetition, may also have enhanced performance after training. The present research sheds light on the neurophysiological mechanisms and temporal characteristics of neurofeedback training and provides evidence for a late manifestation of transfer effects after training.